Perspectives on the Professional Communication Profile and Needs of Emerging Occupational Therapists of the Millennial Generation: A Comparison Study - Ryan Whitney; Peggy Morris; Jessica Harney (Scholarworks @ WMU, 2021)
Background: Millennials, born between 1982 and 2000, became the largest share of the American workforce in 2015. As of 2014, 23.9% of American occupational therapists were under the age of 30. Positive traits ascribed to millennials include: highly educated, ambitious, confident, and optimistic. However, indicators of challenges for managing millennials emerge from media and anecdotal evidence, including stereotypes of disloyalty, entitlement, dependency, and casualness. Relevant for supporting professional development is a call to understand and enhance professional communication. Method: This study analyzed how emerging millennial occupational therapists self-describe their professional communication profile and needs, compared to the perspective of managers, while aiming to describe the accuracy of communication stereotypes. Occupational therapy managers and emerging occupational therapists of the millennial generation completed an online researcher-created survey. Results: Comparison of means revealed statistically significant differences, with the most significance noted on items reflecting professional communication skills of millennial occupational therapists. Conclusion: Analysis of results suggested support for some stereotypes and inaccuracy of others, painting a unique picture of the professional communication profile of millennial occupational therapists. Results from this small-population survey study may inform professional development opportunities for academic and fieldwork educators and occupational therapy managers related to the communication profile and needs of emerging occupational therapists through the lens of generational theory.